The Duty to the Truth: Defense Techniques and Legal Ethics in The Middle Ages and Early Modern Period (Italian Review of Legal History, 2019)
During Middle and Early Modern Ages, the lawyer’s duty to the truth was stated within a wider debate about defense techniques, in which two different concepts of the role of the lawyer as acting as a participant in the administration of justice were discussed. The prohibition to give false or misleading information to the court was certain. The matter all concentrated on the limits of legal argumentation, balancing out the protection of his own client’s interests, with particular regards to the respect of professional secrecy, and the cooperation with the judge in the pursuit of the truth.
Keywords: Lawyer; legal ethics; truth; Middle Ages; Early Modern Ages